Erosive potential of three different commonly used pediatric syrups on deciduous teeth enamel: an in vitro study - Thilak, Neha; Hedge, Sundeep K.; Bhat, Sham S. (International Journal of Contemporary Pediatrics, 2020)
Background: The aim of the study is to compare the erosive potential of three different commonly used pediatric syrups on deciduous teeth enamel. The objectives of the study were to assess the endogeneous pH and titratable acidity of mefenamic acid syrup (meftal P), cetrizine syrup (alerid) and multivitamin syrup (zincovit) and to evaluate the microhardness of the enamel after successive immersion cycles in each of the syrups. Methods: 40 non carious deciduous teeth were included for the study The samples were then randomly allocated into 4 groups (10 in each group): Group A- mefenemic acid syrup (meftal P), Group B- cetrizine syrup (alerid), group C- multivitamin syrup (zincovit) and group D- control (distilled water). The samples were then subjected to the immersion cycles in the syrups. Assessment of enamel surface microhardness was done using Vickers hardness tester at 7th day and 14th day. The pH and titrable acidity of the syrups were also assessed. One way analysis of variance (ANOVA) and post hoc tests were used for the statistical analysis. Results: Out of the test groups, group C showed the lowest pH of around 4.2 and exhibited the largest titrable acidity (22.8 ml) compared with 21 ml in group A and 15.5 ml in group B. At the end of 14th day, group A had microhardness of about 293.43.84±6.34, group B had 299.930±6.85, group C had 313.380±6.23 and group D had 334.190±5.51. Conclusions: All the pediatric liquid medications assessed in the study, meftal P, alerid and zincovit showed acidic pH, high titrable acidities and all the syrups showed loss of microhardness after exposure to the syrups for 14 days. Loss of microhardness was highest for meftal P followed by alerid and least for zincovit.